Ferroelectric properties of Sn-doped PZT-PNN ceramics - K. Sutjarittangtham (2018)
Binary system of 0.45Pb(Zr1/2Ti1/2)O 3-0.55Pb(Ni1/3Nb2/3)O3with a composition close to the morphotropic phase boundary were investigated as a function of Sn doping (0.0-8.0 mole%). X-ray analysis showed that pure perovskite phase was observed for all samples. The density of the ceramic samples was increased with an increase of Sn concentration. However, microstructural analysis showed that Sn-doping has not a significant impact on grain size. Moreover, the increasing Sn-contant can reduce the remanent polarization but increase the dielectic contant. © 2008 Trans Tech Publications, Switzerland.